2012
DOI: 10.1002/j.0022-0337.2012.76.4.tb05274.x
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Power of Web 2.0 Tools: A Wiki Platform as a Multimedia Teaching and Learning Environment in Dental Education

Abstract: This article presents the development and implementation of a wiki-based application for the delivery of educational content in dentistry. The Dental Procedure Education System (DPES) is a new web application that uses SharePoint to combine online collaborative authoring characteristic of wiki spaces with instructional video documentaries. Harnessing the wiki's versatility, DPES offers faculty members an avenue to develop an authoritative source of information for both students, through DPES Pro, and the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…There are many external application tools added to learning of education. Using these applications (wiki chat, video Blog, Google forms or e-learning model linked with student portal system, different adapted programming language, and software applications) all used as inter-conversation online chat that give chance to students to learn from other students [24]; [14]; [29].…”
Section: Introductionmentioning
confidence: 99%
“…There are many external application tools added to learning of education. Using these applications (wiki chat, video Blog, Google forms or e-learning model linked with student portal system, different adapted programming language, and software applications) all used as inter-conversation online chat that give chance to students to learn from other students [24]; [14]; [29].…”
Section: Introductionmentioning
confidence: 99%
“…Facebook was the most cited social media. The reason for posing this question in the study was related to the large number of students who have profiles registered with the site and the fact that the research/professor has begun to explore these new technologies for educational purposes 13 . However, the use of this resource is recent and its real potential in becoming sustainable is not known due to its two-dimensional, non-immersive nature and the limited amount of educational information 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the development of campus‐based relationships using email and instant messaging (IM) networks such as WhatsApp to enhance student‐student and student‐faculty communication, Khatton et al found that students perceived communication with peers as good when using these online tools 20 . Furthermore, Salajan and Mount successfully developed and implemented a Wiki‐based application as an educational tool to promote collaboration in learning for dental faculty, students, and patients 21 …”
Section: Viewpoint 1: Social Media Use Can Benefit Dental Students' Cmentioning
confidence: 99%